An honourable calling political memoirs - Blakeney, Allan (Toronto University of Toronto Press, 2008)
As Premier of Saskatchewan from 1971 to 1982, Allan Blakeney played a pivotal role in the shaping of modern Canada. In this engaging and candid political memoir, Blakeney reflects on his four decades of public service, offering first-hand insights on the introduction of government-sponsored medicare, the patriation of the Canadian Constitution, and new approaches to natural resource development.
Includes index.
Keywords: Blakeney, Allan